Organizational Psychology as a Strategy for Developing Islamic Education Management (Theory and Practice at MTs Persis Lempong Garut) - Fahri Sahrul Ramadhan; Mulyawan Safwandy Nugraha (al-Afkar, Journal For Islamic Studies, 2026)
This research aims to describe the theory and practice of organizational psychology at MTs Persis Lempong Garut, particularly as a strategy for the development of Islamic education management. This study employs a qualitative method, using data collection techniques such as literature review, observation, interviews, and documentation. The results of the research are divided into several discussions, including: the definition and scope of organizational psychology, basic theories of organizational psychology, strategies for applying organizational psychology in Islamic education management, and practices of organizational psychology in Islamic educational institutions.